Pelatihan Pembuatan Pestisida Nabati Untuk Menanggulangi Hama Wereng Di Desa Mojoagung Soko Tuban - Nurul Novitasari; Rinatul Khumaimah; Chilyatul Azkiyya; Ayu Puji Lestari; Azimatul Ulya; Devi Mustika Ramadhani; Elfiana Anggita Dewi; Irma Improatul Fitria; Mastura Laelatul Fajar; Miftakhul Jannah; Nur Aini Lu’luatin; Safira Nurulita; Siti Kholisoh; Siti Qudrotun Nada; Tega Silvia Antika; Romadhotul Fatimah (STIKes Ibnu Sina Ajibarang, 2023)
This community service is carried out to introduce the wider community to the manufacture of vegetable pesticides. This service activity uses a participatory community empowerment approach or Participatory Action Research (PAR). PAR is an approach to research that encourages researchers and people who benefit from research to work together fully in all stages of research. From the activities that have been carried out, activity participants look for the main points that are the biggest problems in the local community, then the KKN-PAR team carries out socialization and action on the agreed problems. After that, assistance to the community. In Mojoagung village, the biggest source of income is a farmer. The main problem of the people in Mojoagung village is the lack of creativity of Mojoagung Village residents in dealing with hereng pests. The people of Mojoagung village still use chemical pesticides to deal with planthopper pests even though in the village environment there are several plants that can be used as ingredients for making vegetable pesticides. However, in Mojoagung Village the use of plant-based pesticides has not been implemented due to a lack of knowledge regarding the manufacture of plant-based pesticides so that people prefer to use chemical pesticides. Based on the explanation above, the KKN-PAR team held an empowerment program regarding the manufacture of plant-based pesticides by utilizing local plant-based materials.